Evaluation of Midnight Salivary Cortisol as a Predictor Factor for Common Carotid Arteries Intima Media Thickness in Patients with Clinically Inapparent Adrenal Adenomas - Giuseppe Reimondo; Barbara Allasino; Marcella Coletta; Anna Pia; Giulia Peraga; Barbara Zaggia; Chiara Massaglia; Piero Paccotti; Massimo Terzolo (International Journal of Endocrinology)
Purpose. The aim of the present study was to investigate the atherosclerotic vascular damage in a consecutive series of patients with AI and to correlate it with MSC. Methods. We studied 32 patients with AI matched with control subjects for age, sex, and cardiovascular risk factors. Either patients or control subjects underwent MSC measurement as outpatients and carotid arteries ultrasound (US) imaging studies. Results. The patients with AI had higher mean carotid artery IMT values and higher MSC levels than control subjects. In a multivariate analysis performed in AI age was the best predictor for IMT. We have stratified patients and control subjects by age (<60 yrs and ≥60 yrs). The patients showed significantly higher MSC levels than controls in both groups, whereas significantly higher IMT values were observed only in older subjects. Conclusions. Patients with AI have signs of accelerated atherosclerosis. Patients older than 60 years seem more susceptible to the possible detrimental effect of subclinical hypercortisolism on cardiovascular system. The MSC levels are not a strong predictor of the accelerated atherosclerosis, but they seem to indicate the subtle but not autonomous cortisol excess that may potentially raise the cardiovascular risk.